Frame by Frame A Materialist Aesthetics of Animated Cartoons - Frank, Hannah (University of California Press, 2019)
For most of the twentieth century, the making of animated cartoons was mechanized and standardized to allow for high-volume production: thousands of drawings were inked and painted onto individual transparent celluloid sheets (called "cels") and then photographed in succession, a labor-intensive process that was divided across scores of artists and technicians, most of them anonymous. In order to understand how the industrial mode of production influenced the medium's visual style, this book regards each frame of a given animated cartoon as a historical document in its own right. This new consideration of the materiality of the medium analyzes cartoons frame by frame to expose hitherto unseen qualities of the image. The book covers the different technologies of reproduction involved in this process, from photography to xerography, as well as the idiosyncrasies of the image-from abstract imagery to mistakes in reproduction-that can be seen only when the film is halted. What emerges is both a new methodology for thinking about animation, the idea of frame-by-frame analysis, and a highly original account of an art formed on the assembly line.